Synthesis of New Amino Acid Conjugates Containing Cinnamic Acid Derivatives and Investigation of Their Cytotoxic and Genotoxic Properties - Sandal, Suleyman; Tekin, Suat; Caliskan, Eray; Koran, Kenan; Gorgulu, Ahmet Orhan; Cetin, Ahmet (Wiley, 2023)
[Abstract Not Available]
Keywords: Cinnamic acid; MTT assay; Comet assay; MCF-7; PC-3; Caco-2